Collective Pride and how it is shown in Gen Z - Nugraha, I Gusti Agung Ananda Giri; Suryanto, Suryanto (Green Publisher Indonesia, 2026)
Collective pride is the feeling of pride that arises when others with whom we identify as a group accomplish an achievement. One of the groups in question is the generation, which is then referred to as generational identity. Each group in social identity theory has its own behavioral characteristics, including how they express pride in both their own achievements and those of others. This study aims to describe the characteristics of Generation Z as a generational identity related to pride. This research uses a qualitative method with a grounded theory approach. Data for this study were obtained through an interview process with three informants. The results of this study found that: 1) the tendency to overthink causes Generation Z to be reluctant to show their pride; 2) Generation Z's attachment to technology makes them show their achievements through social media; 3) Generation Z feels proud of their achievements due to the long process involved; and 4) there is empathetic involvement in the collective pride felt by Generation Z. The study concludes that collective pride in Generation Z is shaped by a combination of internal psychological tendencies, technological engagement, and empathy within a collectivist cultural context, all of which influence both the expression and experience of pride.